History of western philosophy - Russell, Bertrand 1872-1970 (New York Routledge, 1996)
A History of Western Philosophy[1] (1945) by the philosopher Bertrand Russell is a conspectus of Western philosophy from the pre-Socratic philosophers to the early 20th century. Although criticised for its over-generalization and its omissions, particularly from the post-Cartesian period, it was a popular and commercial success, and has remained in print from its first publication. When Russell was awarded the Nobel Prize for Literature in 1950, the book was cited as one of those that won him the award. The book provided Russell with financial security for the last part of his life.